Implementation of Work-Life Balance on Performance - Rasya Hermalya; Dea Damayanti (Yayasan Edukasi Cakrawala Nusantara, 2025)
This research discusses the implementation of balance between work life and personal life (Work Life Balance) on employee performance in companies. This research aims to investigate the effect of implementing work-life balance on employee performance in a company. This research uses descriptive qualitative research methods using theoretical data collection. The research results show that the implementation of work-life balance has a significant influence on employee performance. Employees who have a balance between work life and personal life have better performance compared to employees who do not have this balance. This research also found that factors such as work time flexibility, family support, and company policies that support work-life balance have an important role in improving employee performance